Analyses, simulation and control of a wheeled-vehicle with AWIS (Auxiliary Wheels of Involute-Shape) - Hendra Purnawali (2008)
This project focuses on the development of the wheeled-vehicles by introducing AWIS, which stands for Auxiliary Wheels of Involute-Shape. The introduction of the AWIS to the wheeled-vehicle makes significant contribution towards the development of land-vehicles that have high negotiating movement capabilities on rough terrain while not imposing complexity in design and control. In-depth kinematics, statics, and dynamics analyses are performed on the AWIS. Subsequently, the dynamics simulations and controls of the wheeled-vehicle with AWIS on a flat surface, a block of obstacle, and a flight of stair case, are demonstrated, and the results are evaluated.